Extreme points of ${\mathcal L}_s(^2l_{∞})$ and ${\mathcal P}(^2l_{∞})$ - Kim, Sung Guen (Carpathian Mathematical Publications, 2021)
For $n≥ 2,$ we show that every extreme point of the unit ball of ${\mathcal L}_s(^2l_{∞}^n)$ is extreme in ${\mathcal L}_s(^2l_{∞}^{n+1})$, which answers the question in [Period. Math. Hungar. 2018, 77 (2), 274-290]. As a corollary we show that every extreme point of the unit ball of ${\mathcal L}_s(^2l_{∞}^n)$ is extreme in ${\mathcal L}_s(^2l_{∞})$. We also show that every extreme point of the unit ball of ${\mathcal P}(^2l_{∞}^2)$ is extreme in ${\mathcal P}(^2l_{∞}^n).$ As a corollary we show that every extreme point of the unit ball of ${\mathcal P}(^2l_{∞}^2)$ is extreme in ${\mathcal P}(^2l_{∞})$.